Comprehensive expressional analysis of chemosensitivity‐related markers in large cell neuroendocrine carcinoma of the lung. Issue 20 (28th August 2021) - Ohtaki, Yoichi; Kaira, Kyoichi; Yajima, Toshiki; Erkhem‐Ochir, Bilguun; Kawashima, Osamu; Kamiyoshihara, Mitsuhiro; Igai, Hitoshi; Onozato, Ryoichi; Ibe, Takashi; Kosaka, Takayuki; Nakazawa, Seshiru; Nagashima, Toshiteru; et al.
Abstract: Objectives: Various drug‐sensitivity markers have been reported to be associated with tumor progression and chemotherapy resistance. Detailed expression profiles of sensitivity markers for cytotoxic chemotherapy in pulmonary large cell neuroendocrine carcinoma (LCNEC) remain unclear. Herein, we aimed to clarify the correlation between the expression of drug‐sensitivity markers and clinicopathological features, prognostic impact, and status of tumor immunity in patients with LCNEC. Methods: We retrospectively analyzed the correlation between clinicopathological features and the expression of drug‐sensitivity‐related markers, including vascular endothelial growth factor 2 (VEGFR2), thymidylate synthase (TS), tubulin beta 3 class III (TUBB3), topoisomerase I (Topo‐I), and Topo‐II in 92 surgically resected LCNEC samples. Furthermore, we examined the prognostic significance of expression of these and their correlation with the immune cell status. Results: Overall, high expression of TS, TUBB3, VEGFR2, Topo‐I, and Topo‐II was detected in 50 (54%), 31 (34%), 23 (25%), 65 (71%), and 36 (39%) samples, respectively. Univariate and multivariate analyses revealed that advanced pathological T and N factors, positive lymphatic permeation, and Topo‐II expression were independent unfavorable prognosticators for recurrence‐free survival, and advanced pathological T and N factors, Topo‐II positive expression, and TS positive expression were independent unfavorable prognosticators for overall survival. In terms of correlation with immune cell status, higher expression of VEGFR2 was closely linked to negative PD‐L1 expression. Conclusions: These findings suggest that elevated Topo‐II and TS expression may contribute to poor outcomes through protumoral biology in patients with LCNEC, and elevated VEGFR2 expression might negatively impact tumor immune reactions in LCNEC. Abstract : High expression of chemosensitive markers such as Topo‐II and TS may be responsible for the poor prognosis of LCNEC patients. Furthermore, VEGFR2 expression is negatively correlated with antitumor immune response and may not be just a chemosensitive marker. The expression of chemosensitive markers is an important prognostic factor for LCNEC and may be a biomarker of resistance to overall treatment of lung cancer, such as immune checkpoint inhibitors.